ANALISIS TITIK PULANG POKOK PRODUK OLAHAN COKELAT PADA INDUSTRI RAPOVIAKA SIMPLE DI KOTA PALU - Darwis, Darwis; Muis, Abdul; Howara, Dafina (AGROTEKBIS : JURNAL ILMU PERTANIAN (e-journal), 2023)
The objectives of this study were (i) to determine the production level of Simple Rapoviaka Chocolate Industry at which the break-even point was achieved, and (ii) to determine the income and revenue of the industry at the break-even point. Respondents were purposively selected, including the industry management and its two employees who could provide information about the production process to ensure the accuracy and relevance of the data collected for the research purposes. The research used the Break-Even analysis as its analytical approach. The findings revealed that the break-even point for five variants of chocolate bars is achieved when the production reaches 209 packages, each priced at IDR 18,000 generating a monthly sales of IDR 3,762,000. Similarly, the break-even point for eight variants of chocolate bars is attained at a production of 419 packages, also priced at IDR 18,000 per package generating a monthly sales IDR 7,542,000.